Model Pembelajaran Kooperatif Tipe Student Team Achievement Division Terhadap Peningkatan Keterampilan Proses Sains dan Hasil Belajar Fisika Siswa - Teni Mindawati; Nana Nana (Jurnal Penelitian Pembelajaran Fisika, 2020)
Based on observations in MA Negeri 6 Tasikmalaya, the implementation process of learning physics is still not achieve the maximum results, especially in class X. The main purpose of this study is to describe the increase of KPS and students’ learning achievement in learning physics using a cooperative learning model type Student Team Achievement Division (STAD). This classroom action research has been conducted in three cycles with 30 students of X5 Class of MA Negeri 6 Tasikmalaya. Every cycle consists of planning, action and observation, and reflection. The data were collected using observation sheet for KPS and essay test for learning achievement. Based on the results indicate that the cooperative learning model type STAD effectively could increase KPS and students’ learning achievement in learning physics from cycle to cycle.